A novel Caenorhabditis elegans allele, smn-1(cb131), mimicking a mild form of spinal muscular atrophy, provides a convenient drug screening platform highlighting new and pre-approved compounds. - Sleigh, J; Buckingham, S; Esmaeili, B; Viswanathan, M; Cuppen, E; Westlund, B; Sattelle, D (2011)
Spinal muscular atrophy (SMA), an autosomal recessive genetic disorder, is characterized by the selective degeneration of lower motor neurons, leading to muscle atrophy and, in the most severe cases, paralysis and death. Deletions and point mutations cause reduced levels of the widely expressed survival motor neuron (SMN) protein, which has been implicated in a range of cellular processes. The mechanisms underlying disease pathogenesis are unclear, and there is no effective treatment. Several animal models have been developed to study SMN function including the nematode, Caenorhabditis elegans, in which a large deletion in the gene homologous to SMN, smn-1, results in neuromuscular dysfunction and larval lethality. Although useful, this null mutant, smn-1(ok355), is not well suited to drug screening. We report the isolation and characterization of smn-1(cb131), a novel allele encoding a substitution in a highly conserved residue of exon 2, resembling a point mutation found in a patient with type IIIb SMA. The smn-1(cb131) animals display milder yet similar defects when compared with the smn-1 null mutant. Using an automated phenotyping system, mutants were shown to swim slower than wild-type animals. This phenotype was used to screen a library of 1040 chemical compounds for drugs that ameliorate the defect, highlighting six for subsequent testing. 4-aminopyridine, gaboxadol hydrochloride and N-acetylneuraminic acid all rescued at least one aspect of smn-1 phenotypic dysfunction. These findings may assist in accelerating the development of drugs for the treatment of SMA.